A Study on Impact of Universal Public Distribution System in Tamil Nadu (India) - Mahendran, A (International Journal of Social Sciences and Management, 2014)
PDS is considered as principal institutions in the hands of State Governments for providing safety net to the poor against the spiralling food prices of essential commodities. In this regard Tamil Nadu sets a model in the PDS as universal system. The involvement of the Cooperative Societies, and other distribution networks to make ensures safety net, transparency, accessibility and all reduced the less transaction cost. This study found that problems like leakages, poor quality, under weightiest, non-availability of controlled as well as non-controlled articles during certain times, non-availability of ration cards, bogus cards and its affect the impact of the universal system. This study covered Multi-stage random sampling and pre-test analysis was done. To this study showed that universal PDS will help to provide safety net to the poor. The study suggested that new implications of universal PDS in the state.